The Effect of Overconfidence, Risk Tolerance, Loss Aversion, and Mental Accounting on Crypto Asset Investment Decisions of Generation Z in Yogyakarta - Winata, Wulan; Hermuningsih, Sri; Rinofah, Risal (Universitas Hamzanwadi, 2025)
This study aims to analyze the effect of psychological characteristics, namely overconfidence, risk tolerance, loss aversion, and mental accounting on crypto asset investment decisions in generation z in Yogyakarta City. The method used was a survey with a questionnaire distributed to 100 investors. The results of multiple linear regression analysis show that overconfidence, risk tolerance, and loss aversion have a significant positive effect on investment decisions, while mental accounting does not show a significant effect. The findings emphasize the importance of psychological factors in investment decision-making in the cryptocurrency market, and may provide insights for investors and market practitioners regarding the investment behavior of the younger generation. This study has limitations in terms of sample and data collection methods, which can be taken into consideration for further research.